Student Teachers Readiness and Challenges for Internship Program: A Survey on English Language Education Study Program, Universitas Negeri Jakarta - Fadhilah, Farah Shiba; Mayuni, Ilza; Lasito, Lasito (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2024)
For students majoring in education, the teaching internship program is mandatory. Along with employing the Kurikulum Merdeka in schools, student teachers must also prepare to use it through the teaching internship program. This study aims to investigate student teachers’ readiness and challenges for the teaching internship program. This study employs both quantitative and qualitative methodologies to achieve its objectives. In all, 40 English Language Education Study Program student teachers batch 2020 at Universitas Negeri Jakarta completed questionnaires and participated in Focused Group Discussions focusing on their readiness and challenges based on key teaching competences, enabling competences, professional conduct, and personality. The research uncovered student teachers level of readiness and challenges in 'administration', 'methodology: knowledge and skills', 'assessment', and 'lesson and course preparation' to Kurikulum Merdeka as ‘developing readiness’ and ‘mostly challenging’. However, they perceived ‘approaching readiness’ and views them as ‘mostly not challenging’ aspects as in 'digital media implementation,' 'professional behavior', 'personality', and 'intercultural skills'. Because prior studies did not cover these areas all at once, the knowledge obtained through this research study applies locally.